2002
DOI: 10.1002/cncr.10768
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic and histopathologic diagnosis of equivocal melanocytic skin lesions

Abstract: BACKGROUNDDermoscopy (dermatoscopy, epiluminescence microscopy) is increasingly employed for the preoperative detection of cutaneous melanoma; dermoscopic features of pigmented skin lesions have been previously defined using histopathology as the key to the code. In a preliminary study on 10 cases evaluated by nine dermoscopists and nine histopathologists, the authors experienced that when at least two dermoscopists disagree in evaluating a melanocytic lesion, even histopathologic consultations may give equivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 27 publications
4
57
0
1
Order By: Relevance
“…Among these lesions, we found that a potential source of dermoscopic overestimation was a bandlike dermal infiltrate of melanophages, a common ancillary feature of pigmented spindle-cell nevi. In fact, in 3 cases, this feature was responsible for a diffuse bluish pigmentation of the lesion, a worrisome dermoscopic feature that suggests the presence of either regression 30,31,34 or a blue-whitish veil. 23,30,31 In addition, and even more interestingly, 4 cases showed a striking dermoscopic asymmetry, which was not adequately represented on histologic sections.…”
Section: Asn Either Epithelioid or Spindle-cell Typementioning
confidence: 99%
See 1 more Smart Citation
“…Among these lesions, we found that a potential source of dermoscopic overestimation was a bandlike dermal infiltrate of melanophages, a common ancillary feature of pigmented spindle-cell nevi. In fact, in 3 cases, this feature was responsible for a diffuse bluish pigmentation of the lesion, a worrisome dermoscopic feature that suggests the presence of either regression 30,31,34 or a blue-whitish veil. 23,30,31 In addition, and even more interestingly, 4 cases showed a striking dermoscopic asymmetry, which was not adequately represented on histologic sections.…”
Section: Asn Either Epithelioid or Spindle-cell Typementioning
confidence: 99%
“…Moreover, the histopathologic features of lesions with spitzoid features are often not definitive, creating substantial diagnostic interobserver disagreement. 34 Finally, when dermoscopy clearly reveals features of a Spitz nevus, sometimes the histopathologic analysis of the same lesion supports a diagnosis of a melanoma. Remarkably, the "spitzoid melanoma" does not have a distinctive dermoscopic counterpart.…”
Section: Asn Either Epithelioid or Spindle-cell Typementioning
confidence: 99%
“…We have also called them ‘nevi with regression-like fibrosis’ (NRLF) [2,3,4], a term which maintains ‘regression’ as an immunologic, melanoma-specific phenomenon [5,6,7,8]. Such lesions are probably the result of minor, unnoticed trauma(s) on preexisting nevi and are histopathologically characterized by (i) an atypical junctional proliferation associated with some pagetoid spreading, (ii) significant area(s) of dermal fibrosis/sclerosis containing architecturally atypical melanocytic nests and (iii) residual nevus tissue (often with congenital-like features) around and deep into the cicatricial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In our estimation, the conceptual and practical link between dermoscopy and histopathology is strong. In 2002, Ferrara and colleagues 16 demonstrated in a study of 107 equivocal melanocytic lesions that a diagnostic discrepancy among formally trained dermoscopists seemed to predict a diagnostic disagreement among histopathologists. These data lend increasing importance to establishing a dialogue between dermoscopists and histopathologists who will probably experience similar diagnostic troubles on a given case.…”
Section: Correlation Of Clinical and Dermoscopic Findings With Histopmentioning
confidence: 99%